DNA Methyltransferase 3b Accelerates the Process of Atherosclerosis. (5th April 2022) - Zhu, Ling; Jia, Lei; Liu, Na; Wu, Runmiao; Guan, Gongchang; Hui, Rutai; Xing, Yujie; Zhang, Yong; Wang, Junkui
Abstract : Background. DNA methylation plays a key role in establishing cell type–specific gene expression profiles and patterns in atherosclerosis. The underlying mechanism remains unclear. Previous studies have shown that DNA methyltransferase 3b (DNMT3b) may play an important role in atherosclerosis. This study aimed to establish the regulatory role of DNMT3b in the development of atherosclerosis. Methods. We constructed a viral vector carrying Dnmt3b shRNA to transduce ApoE −/− mice. Meanwhile, healthy human peripheral blood Treg cells were treated with inhibitor of DNMT3b (AZA and EGCG) or transduced with DNMT3b shRNA. Results. It showed that Dnmt3b silencing attenuated atherosclerosis, including decreased lesion size and macrophage content and increased collagen and smooth muscle cells content in ApoE −/− mice. To further investigate the possible mechanisms, combined with previous studies by our group, we showed that Foxp3 -TSDR methylation level was significantly reduced Foxp3 expression and peripheral blood Treg levels were significantly increased by Dnmt3b shRNA vector transduction in animals committed to western diet for 12 and 18 weeks. Consistently, inhibition of DNMT3b (AZA and EGCG) decreased the expression levels of DNMT3b, which can increase the expression levels of FOXP3, and increase the levels of TGF- β and IL-10 and decrease the levels of IL- β and IFN- γ . After transduction with DNMT3b shRNA, the effect was more obvious. Conclusions. DNMT3b accelerated atherosclerosis, and may be associated with FOXP3 hypermethylation status in regulatory T cells.